Effect of electrical pulse forms on the CO(2) reforming of methane using atmospheric dielectric barrier discharge - Song, HK; Lee, H; Choi, JW; Na, BK (SPRINGER, 2004)
Methane conversion using an electric discharge has been studied for many years. Recently, many research groups have developed high-frequency pulsed plasma reaction for methane conversion to higher hydrocarbons and synthesis gas. CO(2) reforming of methane to synthesis gas has also attracted considerable interest as a method of utilization of the greenhouse gases, CO(2) and CH(4), which occupy most of man-made greenhouse gases. In this study, the influence of pulse form of applied voltage on methane and carbon dioxide conversions and product selectivity has been investigated using a cylindrical type DBD reactor. For this purpose, two kinds of power supply were compared, that is, AC power supply which has a high-frequency sinusoidal wave form, and AC pulse power supply which has modified AC pulse wave form. The conversions of methane and carbon dioxide were enhanced using pulsed plasma. The lower pulse width was more profitable economically.
Keywords: HIGHER HYDROCARBONS; CARBON-DIOXIDE; PARTIAL OXIDATION; NONTHERMAL PLASMA; CONVERSION; PRESSURE; PATHWAYS; REACTOR; OXYGEN; CH4